Marital Rape in Denmark and Pakistan: Minorities, Culture and Law - Schultz-Knudsen, Mikele; Mehdi, Rubya (NAVEIÑ REET: Nordic Journal of Law and Social Research, 2021)
This article investigates how rape laws and rape cases are culturally influenced, with a focus on marital rape. The first part of the article looks at cultural influences on rape laws and compares the historical development of these laws in Danish legislation, Pakistani legislation and more broadly in Muslim law. Danish comparative law often compares with legislation in neighboring countries, but comparing to a more different legal system is valuable too. We find that in both Denmark and Pakistan, socio-economic changes challenge existing definitions of rape and marital rape, leading to demands for legal reform, while the legal system tries to maintain as much continuity in the legal definitions as possible. In both jurisdictions, societal views on women and sex also influence how judges and jurors interpret the law, sometimes leading them to contradict the written law. The second part of the article analyzes two court cases involving marital rape in Danish-Pakistani couples. Cultural considerations influenced every part of these court cases, from the questioning of witnesses to the judges’ legal reasoning. Thus, having an understanding of the parties’ culture is important for judges and lawyers. The cases show that culture varies markedly between people from the same national background. Because culture is not uniform, parties are likely to disagree on which cultural rules they followed in their marriage. Judges must be aware that parties may rely on stereotypical cultural views to portray the other party negatively. The article concludes with recommendations, including the need to educate the population as legal concepts of rape change, as well as for judges to be aware of not only the legal culture and the culture of the parties, but also of how their own culture might influence their decisions. The article also reflects on recent legislative changes in Denmark and Pakistan and points out that the debate in Denmark has not considered how consent and threats can have different implications in minority cultures.